Cybersecurity as a strategic priority for Ukraine's integration into the EU digital space - Ippolitov, Yevhenii (Національний технічний університет "Харківський політехнічний інститут", 2025)
This article examines the important role of cybersecurity in Ukraine’s integration into the EU digital space. It examines current challenges, harmonization of legislation with EU standards, and the impact of military aggression on cyber defense. The study highlights key European regulatory acts, Ukraine’s national cybersecurity infrastructure, and international cooperation. Particular attention is paid to the importance of alignment with the NIS2 Directive and GDPR. Strengthening cybersecurity is presented as a critical factor in ensuring Ukraine’s digital resilience and successful European integration.
Keywords: cybersecurity; EU integration; digital security; cyber threats; legislation; cooperation; critical infrastructure